PENGARUH PENGAWASAN BAWASLU DAN PARTISIPASI MASYARAKAT TERHADAP PENCEGAHAN PELANGGARAN PEMILU - Rahmat Ramadhan; Farid Yusuf Nur Achmad; La Asiri (Jurnal Multidisipliner Kapalamada, 2026)
This study aims to analyze the influence of election supervisory agency (bawaslu) supervision and community participation on the prevention of election violations in baubau city. this research employed a quantitative approach using a survey method involving 100 respondents selected through simple random sampling. data were collected through questionnaires and analyzed using ibm spss statistics version 26 with multiple linear regression analysis. the results indicate that bawaslu supervision has a positive and significant effect on the prevention of election violations with a significance value of 0.000 < 0.05. community participation also has a positive and significant effect on the prevention of election violations with a significance value of 0.000 < 0.05. simultaneously, bawaslu supervision and community participation significantly influence the prevention of election violations, with a coefficient of determination (r²) of 50.1%. the findings suggest that strengthening bawaslu supervision and increasing community participation can enhance efforts to prevent election violations in baubau city